2015
DOI: 10.1002/asia.201500238
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Electrocatalysts for All‐Vanadium Redox Flow Batteries

Abstract: Vanadium redox reactions have been considered as a key factor affecting the energy efficiency of the all-vanadium redox flow batteries (VRFBs). This redox reaction determines the reaction kinetics of whole cells. However, poor kinetic reversibility and catalytic activity towards the V(2+)/V(3+) and VO(2+)/VO2(+) redox couples on the commonly used carbon substrate limit broader applications of VRFBs. Consequently, modified carbon substrates have been extensively investigated to improve vanadium redox reactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 94 publications
1
69
0
Order By: Relevance
“…[3,13,14] Carbon-based materials have generally been used as the electrodes for VRBs owing to their low cost, high conduc- tivity and excellent electrochemical/chemical stability.However, the poor kinetics andr eversibility towards both V II /V III and V IV /V V redox couples have caused VRB cells to exhibit large polarizationr esistances in these carbon-based electrodes. Ad ecrease in such resistances can be realized by introducing electrocatalysts on the electrode surfaces to accelerate the redox reactions of the active species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,13,14] Carbon-based materials have generally been used as the electrodes for VRBs owing to their low cost, high conduc- tivity and excellent electrochemical/chemical stability.However, the poor kinetics andr eversibility towards both V II /V III and V IV /V V redox couples have caused VRB cells to exhibit large polarizationr esistances in these carbon-based electrodes. Ad ecrease in such resistances can be realized by introducing electrocatalysts on the electrode surfaces to accelerate the redox reactions of the active species.…”
Section: Introductionmentioning
confidence: 99%
“…[11,[15][16][17][18][19] Additionally,s ome low-costa nd chemically stable metal oxides, such as Mn 3 O 4 , PbO 2 ,N b 2 O 5 ,C eO 2 and WO 3 have also proven to be effective in facilitating vanadiumr edox reactions, but the particles ize, amount and distribution of suchc atalysts on the carbon electrode all seem to be critical to the electrode performance, most likely owing to their poor electronicc onductivity. [28,[30][31][32] In these efforts, the performance of the VRB cells was increased by the addition of these oxygen groupso ru nique nanostructures or both, but the exploration of which oxygen functional groups play ar ole in the improvede lectrochemical performance has not been fully explored. Many researchers have found that not only does nitrogen doping increase the conductivity of carbon materials,b ut it is beneficial for increasing the electron transfer for the vanadium redox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,t he scaling-up of renewable energy-generation systems such as solar cells and wind-powered generators has occurred as ag lobal phenomenon,a nd the demand for highcapability energy storage has increased in modernt imes (i.e., for electric vehicles, factories, energy efficient buildings, etc.). [19] Furthere fforts to reduce the cost and improve the performance of VRFBs should therefore be considered in terms of materials, [20][21][22][23] fabrication processes, [24] and cell configurations. [1] Among the aqueous redox flow batteries (e.g.,L i-I, [2] Zn-polyiodide, [3] Zn/Br, [4a] Zn/Cl, [4b] V-Ce, [5] V-Fe, [6] V-polyhalides, [7] V-Br, [8] organic-inorganic electrolytes, [9] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is essential to minimize the charge-transfer resistance to improve not only the energy efficiency of VRFBs but also the power density,w hich,i nt urn, is effective for cost reduction.C arbonaceous materials such as nanoporous carbon, [1,[20][21][22][23] carbon nanotubes, [32] graphenes, [33] and nitrogen-doped carbons [34] and their composites [21] have been evaluated for use in VRFBs owing to their advantages of high surfacea rea, good electrical conductivity,f lexible and easy processing, relatively low cost, and good stabilityi nt he highly acidic electrolyte solution. Thus, it is essential to minimize the charge-transfer resistance to improve not only the energy efficiency of VRFBs but also the power density,w hich,i nt urn, is effective for cost reduction.C arbonaceous materials such as nanoporous carbon, [1,[20][21][22][23] carbon nanotubes, [32] graphenes, [33] and nitrogen-doped carbons [34] and their composites [21] have been evaluated for use in VRFBs owing to their advantages of high surfacea rea, good electrical conductivity,f lexible and easy processing, relatively low cost, and good stabilityi nt he highly acidic electrolyte solution.…”
Section: Introductionmentioning
confidence: 99%
“…For many electrode reactions with sluggish kinetics, catalysts are needed to reduce the polarization (i.e. to improve the voltage efficiencies) and to improve the reaction rate ( Table 3) [23]. Catalysts are generally applied onto a porous material, which offers high contact area for electrolytes.…”
Section: Redox Electrochemistry Of Flow Batteriesmentioning
confidence: 99%